Booklet-Based Education as an Intervention to Improve Caregiver Knowledge & Behavior in Tuberculosis Prevention in Children - Anda Syahputra; Fitriani Agustina; Syahabuddin Syahabuddin; Marlina Marlina; Halimatussakdiah Halimatussakdiah; Kayyisah Indah Sahqila (Poltekkes Kemenkes Aceh, 2026)
Background: Tuberculosis (TB) in children remains a public health problem due to the high risk of transmission after close contact with adult TB patients, especially within families. Household-based prevention requires adequate knowledge and behavior from caregivers. Booklets can be used as educational tools because they present information systematically, are easy to understand, can be studied independently, and can be reread. Purpose: Analyzing the influence of health education using booklets on caregiver knowledge and behavior in preventing TB in children. Methods: This quasi-experimental study with a one-group pretest–posttest design involved 38 caregivers of TB patients' families at the Muara Dua Community Health Center, Lhokseumawe City, selected using the Total Sampling Technique. The intervention provided was health education using a booklet, each lasting 30 minutes over two sessions. Measurements were taken before the intervention and seven days after the intervention using a knowledge and behavior questionnaire consisting of 15 questions. Data were analyzed using a paired t-test with a significance level of 0.05. Results: The mean knowledge score increased from 4.16 ± 1.386 to 13.08 ± 1.260, with a mean increase of 8.921 points (p<0.001). The mean behavior score increased from 4.05 ± 1.627 to 12.50 ± 1.736, with a mean increase of 8.447 points (p<0.001). These findings indicate a significant increase in caregiver knowledge and behavior after being given booklet-based health education. Conclusion: Health education using booklets has the potential to improve caregivers' knowledge and behavior regarding TB prevention in children. This medium can be considered a practical and sustainable educational tool to strengthen family-based TB prevention.